Factors influencing the development of public secondary school libraries in the third district of Quezon City - Totanes, Vernon R. (Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study focused on the factors influencing the development of public secondary school libraries (PSSLs) in the Third District of Quezon City (TDQC). It sought to determine the PSSLs' level of development by using the "Guidelines on the Implementation of School Library Policies and programs" (hereafter referred to as the 1998 Guidelines) -- issued in 1998 by the then Department of Education, Culture and Sports--as a means to come up with a Development Score (DS) for each of the PSSLs, and then identified the factors that influenced the development of the PSSL with the highest DS.